Carbon Coating Stability on High-Voltage Cathode Materials in H2O-Free and H2O-Containing Electrolyte. Issue 7 (1st January 2015) - Metzger, Michael; Sicklinger, Johannes; Haering, Dominik; Kavakli, Cüneyt; Stinner, Christoph; Marino, Cyril; Gasteiger, Hubert A.
Abstract : Carbon coatings on cathode materials with low electrical conductivity like phospho-olivines LiMPO4 (M = 3d-transition metal) are known to improve their performance in Li-ion batteries. However, at high potentials and in the presence of water, the stability of carbon coatings on high-voltage materials (e.g., LiCoPO4 ) may be limited due to the anodic oxidation of carbon. In this work, we describe the synthesis of LiFePO4 (LFP) with an isotopically labeled 13 C carbon coating (characterized by Raman spectroscopy, electrical conductivity, and charge/discharge rate capability tests) as a model compound to study the anodic stability of carbon coated cathode materials in ethylene carbonate-based electrolytes. We characterize the degradation of the 13 C carbon coating by On-line Electrochemical Mass Spectrometry (OEMS) through the 13 CO2 and 13 CO signals in order to differentiate the anodic oxidation of the coating ( 13 C) from the oxidation of electrolyte, conductive carbon, and binder (all 12 C) in the electrode. The oxidation of the carbon coating takes place at potentials ≥ 4.75 V for electrolyte without H2 O (< 20 ppm) and ≥ 4.5 V for electrolyte with 4000 ppm H2 O, and it is strongly enhanced for H2 O-containing electrolyte. The extent of carbon coating oxidation over 100 h at 4.8 and 5.0 V vs. Li/Li + (25°C) is projected on the basis of our OEMS data, suggesting that carbon coatings have insufficient stability at such high cathodic potentials. Furthermore, our results prove the in situ formation of H2 O during the anodic decomposition of ethylene carbonate-containing electrolyte. The H2 O formation is monitored via the detection of gaseous POF3, which is formed from the reaction of LiPF6 with H2 O.